Spinonin, a novel glycoside from Ononis spinosa subsp leiosperma - (:unkn) unknown (AMER CHEMICAL SOC, 1997)
The roots of Ononis spinosa subsp. leiosperma (Leguminosae) afforded a new glycoside, spinonin (1), possessing a novel skeleton, in addition to the known isoflavonoid glycoside, ononin [7 beta-(glucosyloxy)formononetin] (2) and the known pterocarpan, 7-demethoxy-7-D-(glucosyloxy)-homopterocarpin (3). The structure of the new isolate was elucidated by spectral methods including H-1 and C-13 NMR, COSY, APT, HETCOR, HMBC, NOESY, CD, FABMS, HRMS, EIMS, CIMS, and some chemical reactions. Spinonin was inactive against a number of human cancer cell Lines and HIV-1 reverse transcriptase. The compounds 1 and 3 showed weak activity against Pseudomonas aeruginosa, whereas 2 was active against beta-hemolytic Streptococcus.
Keywords: RESORCINOL DERIVATIVES; ALKYLRESORCINOLS; COMPONENTS; VISCOSA; NATRIX